Efeito da fadiga no andar de pacientes com doença de Parkinson: relação com o nível de atividade física - Santos, Paulo Cezar Rocha dos [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The symptom of fatigue and the muscle fatigue are both considered as problems that can attack patients with Parkinson disease (PD), which can have influence on gait. Physical activity counteracts the commitments of the PD and the effects of fatigue. However, the relationship between the level of physical activity and the fatigue in patients compared to individuals without PD is not very clear as well as the influence of induced fatigue on gait parameters in regular room and on the floor with overdrive obstacle PD patients. To fill these gaps 3 studies were proposed: Study 1 that aims to relate the symptom of fatigue with physical activity level in patients with PD and in individuals not affected by PD as to compare the perception of fatigue between these two groups. This study was composed by the participation of 80 individuals, in which 40 were patients with PD and 40 were patients without the disease (group control). Participants, within their groups, were divided into active (20) and inactive (20) according to the Baecke Questionnaire that was modified for the elderly. The Multidimensional Fatigue Inventory was used to verify the subjective perception of fatigue in both groups. Two-way ANOVA was used to compare groups according to the levels of physical activity and the Pearson correlation test that was performed to verify the relationship between physical activity level and subjective perception of fatigue for each group. There was only one difference which was between the fatigue of the participants with PD compared with controls without effect on physical activity level. Still, there was no relationship between level of physical activity and perception of fatigue. Patients with PD have a higher perception about the symptom of fatigue on overall dimensions, physical, low motivation, mental and reduced level of physical activity, when compared with the control individuals; Study 2 and 3 aim to analyze the effect of muscle fatigue on...

O sintoma da fadiga e a fadiga muscular são considerados problemas que acometem pacientes com doença de Parkinson (DP), podendo influenciar no andar. A atividade física se contrapõe aos comprometimentos da DP e aos efeitos da fadiga. Entretanto, o relacionamento entre o nível de atividade física e fadiga em pacientes com DP comparados com indivíduos sem DP não se faz claro, bem como, a influência da indução à fadiga nos parâmetros do andar em ambiente regular e no andar com ultrapassagem de obstáculo de pacientes com DP. Para preencher essas lacunas, 3 estudos são propostos. O estudo 1 objetivou relacionar o sintoma da fadiga com o nível de atividade física em pacientes com DP e em indivíduos não acometidos pela DP e comparar a percepção de fadiga entre os grupos. Participaram deste estudo 80 indivíduos, sendo 40 pacientes com DP e 40 indivíduos sem DP (controle). Os participantes, dentro de seus grupos, foram distribuídos em ativos (20) e inativos (20) de acordo com o Questionário de Baecke modificado para idosos. O Multidimensional Fatigue Inventory foi utilizado para verificar a percepção subjetiva da fadiga em ambos os grupos. ANOVA two-way foi utilizada para comparar os grupos de acordo com os níveis de atividade física e o teste de correlação de Pearson foi realizado para verificar a relação entre o nível de atividade física e percepção subjetiva de fadiga para cada grupo. Houve diferença apenas entre a percepção de fadiga dos participantes com DP quando comparados ao controle, sem efeito para nível de atividade física. Ainda, não houve relação entre nível de atividade física e a percepção de fadiga. Pacientes com DP apresentam maior percepção do sintoma da fadiga nas dimensões geral, física, baixa motivação, nível de atividade reduzida e mental, quando comparados com indivíduos controle. Os Estudos 2 e 3 objetivaram analisar o efeito da fadiga muscular nas variáveis cinemáticas,...
Keywords: Cinesiology; Cinesiologia; Parkinson, Doença de; Aptidão física; Fadiga